Numerical investigation of the effects of geometric and fluid parameters on the thermal performance of a double -tube spiral heat exchanger with a conical turbulator - Seyed Hossein Hashemi Karouei; Walaa Nasser Abbas; Mohammed Ali; Dhuha Radhi Nayyef; Karrar K. Abdul Hussein; Karrar A. Hammoodi; Seyed Saeed Hosseini Azizi (Case Studies in Thermal Engineering)
One of the most important principles in heat exchangers is to increase heat transfer and minimize pressure drop. In the present work, a two-tube spiral heat exchanger equipped with a conical turbulator is considered. In the first part of this analysis, the diameter of the inner spiral coil was investigated. In the second part of the study, the effect of the type of working fluid on heat transfer and the hydrodynamic factors of the fluid were investigated. In the first part of the study, the results showed that the highest value of thermal performance was at the lowest Reynolds number and the value of thermal performance at this Reynolds number (Reynolds = 250) was for diameters of 42 mm, 46 mm. and 50 mm was 35, 20 and 30 percent higher than the number 1. In the second part of the study, the results showed that the thermal performance values for Water/SWCNT_MWCNT, Water/Al2O3_TiO2 and pure water were 39 %, 37 % and 35 % higher than 1, respectively, which indicates the great effect of the conical turbulator and nanohybrid fluids in improving heat transfer. This study showed that the use of the innovative conical turbulator significantly improves heat transfer and increases the efficiency of the studied double-tube spiral heat exchanger. Therefore, the use of the conical turbulator has a significant effect on increasing the thermal performance of the intended heat exchanger and the use of this type of turbulator is recommended in the industry.